Vulneración laboral a trabajadores contratados por modalidad CAS luego de la vigencia de la Ley 29849, en Hospital Regional de Huancavelica año 2014 - Huamani Santiago, Marcelino (2022)
The conducted research falls within the basic type, aiming to address broad and universally applicable issues. In this context, basic research seeks to contribute to theoretical advancement, focusing on generating new knowledge without necessarily addressing immediate practical applications. In this study, the level of job vulnerability of workers hired under the Administrative Service Contract (CAS) modality was examined after the enactment of Law 29849. The research design was non-experimental, adopting a simple descriptive approach. Its objective was to determine the level of job vulnerability of workers hired under the CAS modality after the implementation of Law 29849 at the Regional Hospital of Huancavelica in the year 2014. The sample, selected probabilistically, included 84 workers under the CAS modality at the mentioned hospital. The main results revealed that 20% (17) of workers hired under the CAS modality experienced violations of their labor rights after the enactment of Law 29849 in 2014. On the other hand, 80% (67) of them did not suffer violations of their labor rights. Some areas were identified where violation occurred, such as the right to a 24-hour rest, break time, social security, and union freedom. The analysis of the Student's T-test supported the existence of violations in labor rights, endorsing the alternative hypothesis at a significance level of 5%. However, upon comparison with the vulnerability table, it was concluded that the level of job vulnerability was low..